Muskox body temperature and activity data - Schmidt, Niels Martin (Zenodo, 2019)
Data on muskox ( Ovibos moschatus ) body temperature (°C) (mean, range, max and min) and activity (mean count) from Zackenberg in Northeast Greenland collected every 4 hours during the period from autumn 2017 to autumn 2018. : Additional data added